2022
DOI: 10.21037/tlcr-22-247
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 2 expression in early-stage non-small cell lung cancers identifies patients with good prognosis and longer survival

Abstract: Background: Non-small cell lung cancer (NSCLC) is a leading cause of cancer-related death with a 5-year survival of only 21%. Reliable prognostic and/or predictive biomarkers are needed to improve NSCLC patient stratification, particularly in curative disease stages. Since the endogenous cannabinoid system is involved in both carcinogenesis and anticancer immune defense, we hypothesized that tumor tissue expression of cannabinoid 1 and 2 receptors (CB1 and CB2) may affect survival.Methods: Tumor tissue samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The reason could be that apart from the limiting psychotic effects of cannabinoid agonists through activation of CB-1R in the test candidate's central nervous system, the results of many studies are discrepant on whether cannabinoid receptor activation inhibits or enhances tumor development and progression. Vidlarova et al 47 found that tumors expressing CB-2R mRNA were associated with significantly longer overall, cancer-specific, and disease-free survival, whereas CB-2R protein expression was associated with a less advanced disease stage and grade. Similar results were observed in hepatocellular carcinomas; increased expression of CB-1R and CB-2R significantly related to disease-free survival and was associated with histologically well-differentiated tumors as well as less portal vein involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The reason could be that apart from the limiting psychotic effects of cannabinoid agonists through activation of CB-1R in the test candidate's central nervous system, the results of many studies are discrepant on whether cannabinoid receptor activation inhibits or enhances tumor development and progression. Vidlarova et al 47 found that tumors expressing CB-2R mRNA were associated with significantly longer overall, cancer-specific, and disease-free survival, whereas CB-2R protein expression was associated with a less advanced disease stage and grade. Similar results were observed in hepatocellular carcinomas; increased expression of CB-1R and CB-2R significantly related to disease-free survival and was associated with histologically well-differentiated tumors as well as less portal vein involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Because CB2 expression has been linked to longer survival in both lung [ 15 ] and hepatocellular cancer [ 16 ], similar mechanisms may be active in PDAC. In particular, CB2 is a likely target for endo- and exocannabinoids with anticancer activity resulting from effects on motility and migration, reductions in invasiveness and angiogenesis, and the induction of apoptosis [ 17 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative RT-PCR reactions were performed in LightCycler 384 Multiwell plates (Roche, Basel, Switzerland). In each reaction, 50 ng of cDNA was mixed with LightCycler 480 DNA Probes Master (Roche, Basel, Switzerland) and the appropriate TaqMan Gene Expression Assay (Life Technologies, Thermo Fisher Scientific, Waltham, MA, USA; CB1: Hs01038532_m1; CB2: Hs00275635_m1; OPRK: Hs00175127_m1; OPRD: Hs00538331_m1; OPRM: Hs01053957_m1; OPRL: 00173471_m1; OGFR: Hs01071266_m1; ACTB: Hs99999903_m1) [ 15 ]. The volumes of the reagent mixture and the sample were 9 µL and 1 µL, respectively, and each sample was applied to the plate in four replicates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was registered at ClinicalTrials.gov (NS10285). A total of 166 patients were prospectively enrolled in the study, which was conducted between August 2009 and April 2013 ( 26 ). However, 47 patients were excluded (R>0, histologically not NSCLC, stage IIIB–IV, neoadjuvant chemotherapy, death caused by perioperative complications), finally 119 patients were analyzed ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%